Checklist of psychological variables involved in climbing. Operationalizing expert’s knowledge - Santolaya, M; Rubio, V.; Ruiz-Barquín, R. (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In climbing both technical and physical skills have proven to be highly demanding and plenty of research has been done to prove so, but, coaches and climbers claim that psychological factors play a determining role and are key for high performance. It becomes necessary to develop new strategies to established empiric or theoretical base to support psychology to be applied to climbing. The aim of this study was to identify psychological variables needed to improve and excel as a climber and to operationalize implicit expert knowledge. To this end, using a mixed quantitative-qualitative method, four Spanish high-level coaches were interviewed and participated in a three-round focus group. Results found were organized and grouped according to the model of psychological dimensions proposed by Sánchez & Torregrosa in order to create an assessment tool that provides coaches information about climber’s mental skills follow up. The final result was the creation of a Mobile APP checklist of psychological variables involved in climbing that can provide real time performance information, share individual climber’s follow-up and comparison with other climbers. Future lines of research were proposed for the improvement of assessment tools for psychological skills in climbing that can help coaches and trainers to record, enhance and predict performance.